Medical-surgical nursing : an integrated approach - White, Lois; Baumle, Wendy; Duncan, Gena (Delmar Cengage Learning, 2013)
"Medical-surgical nursing: an integrated approach 3-Eis a comprehensive, reader friendly resource for the practical/vocational nursing student. The 3rd Edition has been completely reinvisioned and thoroughly updated in all aspects of its coverage, with chapters now broken out into smaller, more manageable portions. In addition to rich coverage of all body systems with anatomy & physiology, data collection, disease information, and a strong focus on the nursing process, exciting new chapters on family processes and issues, psychobiological issues, bioterrorism and more have been added. Engaging features including case studies, critical thinking exercises, evidence-based practice boxes, informatics boxes, memory tricks, and more support student learning and retention throughout the text. NCLEX style questions and Theory to Practice activities provide opportunities to test understanding and apply concepts. This is the ideal choice for instructors looking for depth of coverage and student-focused features."--Publisher's website